NUMERICAL STUDIES ON THE GAP RESONANCE OF FPSO AND SHUTTLE TANK SIDE BY SIDE DUE TO OCEAN EXCITING WAVES - ABD JALIL, MUHAMMAD NURTASLIM (Universiti Teknologi PETRONAS, 2017)
This research is proposed to study the gap resonance of FPSO and shuttle tank in side by side arrangement due to exciting waves. During the side by side arrangement, there are a gap distance between the FPSO and shuttle tank which resonance might occurs. This resonance can increase the wave height in the gap distance that can disrupt the arrangement side by side of FPSO and shuttle tank. This study is crucial because the FPSO and shuttle tank in this arrangement is designed to undergo the offloading operation. If these arrangement is disrupted due to the resonance, the effectiveness of the offloading operation will reduce as well as the safety of the crew because the FPSO and shuttle tank might be colliding. Thus, the ability of the FPSO and shuttle tank to maintain the arrangement and gap distance will be the significant factor in obtaining the effectiveness of the offloading operation and safeness. The simulation of the FPSO and shuttle tank in the Star CCM+ software will be done to analyse the gap distance and drafts of two floating bodies on the resonance. Furthermore, this study also aims to analyse the dynamic response and environmental loading on these two floating bodies.